2003
DOI: 10.1016/s1077-3142(03)00081-x
|View full text |Cite
|
Sign up to set email alerts
|

Facial expression recognition from video sequences: temporal and static modeling

Abstract: The most expressive way humans display emotions is through facial expressions. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
419
0
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 761 publications
(434 citation statements)
references
References 26 publications
2
419
0
13
Order By: Relevance
“…There are many different techniques being currently applied to the problems of automatic facial expression recognition and automatic FACS coding such as: Expert Systems [16], Hidden Markov Models [7], Gabor filters [6,17,18,19,20,21,22,23,24] and Optical Flow Analysis [25]. For an overview of the current techniques see [26].…”
Section: Computer Vision Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different techniques being currently applied to the problems of automatic facial expression recognition and automatic FACS coding such as: Expert Systems [16], Hidden Markov Models [7], Gabor filters [6,17,18,19,20,21,22,23,24] and Optical Flow Analysis [25]. For an overview of the current techniques see [26].…”
Section: Computer Vision Approachesmentioning
confidence: 99%
“…Recent research has shown that it is not just the expression itself, but also its dynamics that are important when attempting to decipher its meaning [4,5,6,7,8,9,10]. The dynamics of facial expression can be defined as the intensity of the AUs coupled with the timing of their formation.…”
Section: Introductionmentioning
confidence: 99%
“…Most of researches have been done on dynamic textures [7,8,9,10,11,12,13]. [14] Study showed to accept fine grained diversity in facial expression on the basis of Facial Action Coding System (FACS) and action units (AUs).…”
Section: Introductionmentioning
confidence: 99%
“…Techniques for automating the analysis of facial expressions [10][11][12] are critical to the realization of more natural and effective human-computer interactions, which can add to existing studies of human emotion and affective computing and enhance applications in a broad range of areas. In a given case, however, a false expression can be interpreted as a true expression because the user may be hiding their genuine emotion.…”
Section: Introductionmentioning
confidence: 99%